Presence of pap-, sfa-, and afa-related sequences in necrotoxigenic Escherichia coli isolates from cattle: evidence for new variants of the AFA family. - Mainil, J G (1997)
Necrotoxigenic Escherichia coli (NTEC) are associated with intestinal and extraintestinal diseases in animals and human beings and produce Cytotoxic Necrotizing Factor 1 (CNF1) or 2 (CNF2). Fourty-three NTEC1, 42 NTEC2, and 32 CNF-negative isolates from cattle were tested by colony DNA hybridization, by plasmid DNA hybridization and by PCR assays for the presence of DNA sequences homologous to the operons coding for fimbrial (PAP/PRS, SFA/FIC, and F17) and afimbrial (AFA/Dr) adhesins of extraintestinal E. coli. Most NTEC1 isolates hybridized with the PAP probes and either the SFA probe (37%) or the AFA probes (49%). Most NTEC2 isolates, in contrast, hybridized with the F17 probe (45%), the AFA probes (19%), or the F17 and AFA probes (22%). A probe-positive plasmid was identified in each of the 19 NTEC2 isolates studied. They all hybridized with the CNF2 toxin probe (Vir plasmids) and most of them with the F17 (6 plasmids) or AFA (7 plasmids) probes. PCR amplification was obtained with 6 of the 11 NTEC isolates tested for the papGII/prsG genes; with all 5 NTEC isolates tested for the sfa and related operons; but with none of the 18 NTEC isolates tested for the afa and related operons. pap-, sfa-, and afa-related sequences are thus present in NTEC isolates from cattle in addition to f17-related operons and may code for adhesins corresponding to specific colonization factors. f17- and afa-related sequences can be located on the Vir plasmids along with the cnf2 gene. Existence of new variants of the AFA/Dr family is evident from the negative results of this family-specific PCR assay.